1883 Kan. Sess. Laws 159, ch. 105, §§ 1–2 - (:unkn) unknown (General Publisher, 1883)
Prohibited the selling, trading, giving, or loaning of a pistol, revolver, or toy pistol, dirk, Bowie knife, brass knuckles, slungshot, or other dangerous weapons to any minor, or to any person of notoriously unsound mind. Also prohibited the possession of such weapons by any minor. Punishable by fine of $5-100. Also prohibited a minor from possessing a pistol, revolver, toy pistol by which cartridges may be exploded, dirk, Bowie knife, brass knuckles, slungshot, or other dangerous weapon. Punishable by fine of $1-10.
--
Keywords: POSSESSION - MINORS